2010
DOI: 10.1530/eje-09-0800
|View full text |Cite
|
Sign up to set email alerts
|

Persistent increase of osteoprotegerin levels after cortisol normalization in patients with Cushing's syndrome

Abstract: Objective: Osteoprotegerin (OPG) has been identified as a decoy receptor that inhibits osteoclast differentiation and, more recently, as a paracrine regulator of vascular calcification. OPG is suppressed by glucocorticoids (GC); however, results from experimental and clinical studies are not univocal. The aim of this study was to evaluate OPG and bone metabolism in patients with Cushing's syndrome (CS) before and after cure. Design and methods: Twenty-six patients with CS (all women, mean age: 39.1G11.9 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
(46 reference statements)
1
11
0
1
Order By: Relevance
“…However, although we cannot establish if the TXNIP in bone is increased in active CS, the strong correlation between TXNIP and TRX, as well as the markedly elevated TRX levels compared with control at baseline, may suggest so. The OPG/RANKL system is of major importance for the coordinated coupling principle in bone remodeling (4,23). We found that silencing of TXNIP in hFOB decreased OPG and increased RANKL, indicating that decreased OB expression of TXNIP favors bone resorption.…”
Section: Discussionmentioning
confidence: 77%
“…However, although we cannot establish if the TXNIP in bone is increased in active CS, the strong correlation between TXNIP and TRX, as well as the markedly elevated TRX levels compared with control at baseline, may suggest so. The OPG/RANKL system is of major importance for the coordinated coupling principle in bone remodeling (4,23). We found that silencing of TXNIP in hFOB decreased OPG and increased RANKL, indicating that decreased OB expression of TXNIP favors bone resorption.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, elevated levels of total cortisol were associated with low levels of TRAIL also in the CB although this association did not reach statistical significance. In addition, a previous study demonstrated that pathological levels of cortisol increase the circulating levels of osteoprogerin, a neutralizing receptor for TRAIL [33]. In relationship with the potential vasoprotective activity of TRAIL [15][18], it remains to be established whether the drop of TRAIL after partum associated to stressful conditions represents a risk for future cardiovascular disease, which, anyhow, is rare at the age of the women enrolled in our study.…”
Section: Discussionmentioning
confidence: 79%
“…Earlier views on its pathogenesis stressed the extraskeletal effects of glucocorticoids, such as hypogonadotrophic hypogonadism, a decrease in intestinal calcium absorption and an increase in renal calcium excretion, resulting in secondary hyperparathyroidism. At variance, several studies found normal PTH levels in patients with CS . The administration of exogenous glucocorticoids and most forms of primary adrenal CS result in decreased secretion of adrenal androgens and oestrogens, and changes in the GH–IGF1 axis and insulin .…”
Section: The Pathogenesis Of Bone Disease In Endogenous Cushing's Synmentioning
confidence: 99%
“…Glucocorticoids increase the expression of receptor activator of nuclear factor‐κB ligand (RANKL), while the expression of osteoprotegerin (OPG) is decreased . Interestingly, however, measurement of circulating RANKL and OPG concentrations does not reflect their bone tissue expression, with OPG levels increased in patients with chronic hypercortisolism and persisting even after successful surgical treatment of CS; the source of increased OPG level in patients with CS is probably the vascular endothelium and may correlate with the increased cardiovascular risk of these patients rather than their bone status …”
Section: The Pathogenesis Of Bone Disease In Endogenous Cushing's Synmentioning
confidence: 99%